Multicenter prospective cohort study of adverse events associated with biliary endoscopic retrograde cholangiopancreatography: Incidence of adverse events and preventive measures for post‐endoscopic retrograde cholangiopancreatography pancreatitis. Issue 6 (4th February 2022) - Fujita, Koichi; Yazumi, Shujiro; Matsumoto, Hisakazu; Asada, Masanori; Nebiki, Hiroko; Matsumoto, Kazuya; Maruo, Toru; Takenaka, Mamoru; Tomoda, Takeshi; Onoyama, Takumi; Kurita, Akira; Ueki, Toshiharu; et al.
Abstract : Objectives: The reported incidence of adverse events (AEs) in endoscopic retrograde cholangiopancreatography (ERCP) varies between 2.5% and 14%. The aim of this study was to evaluate the incidence and severity of AEs in biliary ERCP and to specify the risk factors and preventive measures for post‐ERCP pancreatitis (PEP). Methods: Patients with biliary disease with intact papilla were prospectively enrolled at 36 hospitals between April 2017 and March 2018. The primary outcomes were the incidence and severity of AEs. Results: A total of 16, 032 ERCP procedures were performed at the 36 hospitals during the study period and 3739 patients were enrolled. The overall incidence of AEs was 10.1% and ERCP‐related mortality was 0.08%. PEP developed in 258 cases (6.9%), bleeding in 33 (0.9%), instrumental AEs in 17 (0.5%), infections in 37 (1.0%), cardiovascular AEs in eight (0.2%), pulmonary AEs in eight (0.2%), drug reaction AE in one (0.03%), pain in 15 (0.4%), and other AEs in 15 (0.4%). Multivariable analysis showed significant risk factors for PEP were: female of younger age, pancreatic guidewire‐assisted biliary cannulation, temporary guidewire insertion into the pancreatic duct, total procedure time >60 min, and post‐ERCP administration of non‐steroidal anti‐inflammatory drugs. Effective preventive measures were prophylactic pancreatic stenting (PPS) and epinephrine spraying onto the papilla. Conclusions: In patients with intact papilla who underwent biliary ERCP, the incidence of AEs was 10.1% and the mortality was 0.08%. PPS and epinephrine spraying may prevent PEP. Registration: This study was registered in the University Hospital Medical Information Network (UMIN000024820).